Inovasi Pengolahan Limbah Industri Pemindangan Menjadi Biogas: Solusi Pencemaran Sungai di Desa Watulimo, Trenggalek - Irawan, Dani; Thohir, M. Anas; Wulandari, Retno; Yafie, Evania (Abdimas Indonesian Journal, 2024)
The scanning industry is one of the industries that produces organic waste in both solid and liquid forms. However, the scanning industry waste that has the greatest impact on the environment is liquid waste. In one of the areas with quite high pollution conditions in the scanning industry, namely Watulimo Village, Trenggalek. The objectives of this community service activity are (1) To install a portable digester in an effort to process scanning waste into biogas, (2) To provide technical guidance on the stages of processing scanning wastewater so that in the future they can independently process wastewater from the scanning industry. The methods used include presentations, discussions, demonstrations, and practicums. The results of this activity are (1) The installation of a portable digester in processing scanning waste into biogas in Watulimo Village has proven effective in processing organic waste into a renewable energy source, (2) Through technical guidance on the stages of processing scanning wastewater, the people of Watulimo Village are equipped with the ability to manage waste independently